2021
DOI: 10.1007/s13668-021-00380-2
|View full text |Cite|
|
Sign up to set email alerts
|

The Nutrition-COVID-19 Interplay: a Review

Abstract: Purpose of Review Nutritional status is affected by the COVID-19 pandemic, directly or indirectly. Even with the recent rollout of the coronavirus disease 2019 (COVID-19) vaccines and availability of medicines such as remdesivir, and monoclonal antibodies, host nutritional status is pivotal in the fight against the acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and outcomes. The purpose of this review is to discuss the effects of COVID-19-related lockdown on lifestyle behaviors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 81 publications
0
39
0
2
Order By: Relevance
“…These comorbidities have in common chronic systemic inflammation, a higher prevalence of sarcopenia, loss of lean body mass, and protein-calorie malnutrition, which impairs immunity to infectious agents, such as SARS-CoV-2 [ 4 , 5 , 6 , 7 , 8 ]. The COVID-19 pandemic has heightened the risks of sarcopenia and protein-calorie malnutrition due to restrictions in physical activity from lockdowns, inaccessibility to exercise facilities, limited public transportation, and food insecurity from supply chain disruptions [ 9 ]. Symptomatic infection by SARS-CoV-2 results in a catabolic inflammatory response coupled with inherent physical immobility, poor nutrient intake from dysgeusia and anosmia, and frequent gastrointestinal involvement [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These comorbidities have in common chronic systemic inflammation, a higher prevalence of sarcopenia, loss of lean body mass, and protein-calorie malnutrition, which impairs immunity to infectious agents, such as SARS-CoV-2 [ 4 , 5 , 6 , 7 , 8 ]. The COVID-19 pandemic has heightened the risks of sarcopenia and protein-calorie malnutrition due to restrictions in physical activity from lockdowns, inaccessibility to exercise facilities, limited public transportation, and food insecurity from supply chain disruptions [ 9 ]. Symptomatic infection by SARS-CoV-2 results in a catabolic inflammatory response coupled with inherent physical immobility, poor nutrient intake from dysgeusia and anosmia, and frequent gastrointestinal involvement [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, diet can significantly prevent or induce low-grade inflammation [ 60 , 61 ]. Eating a high amount of ultra-processed energy-dense and other unhealthy food with a low amount of healthy nutrients can cause low-grade inflammation and increase the risk of infections and other immune-related disorders [ 62 , 63 ]. In this context, it has been shown that a lifestyle switch to no exercise and consuming an unhealthy diet for only two weeks has already resulted in reduced insulin sensitivity, a higher level of body fat, and low-grade inflammation [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is important to note that only attaining a normal, healthy bodyweight will likely not be sufficient to promote adequate immune fitness. Mental health (e.g., stress reduction), healthy nutrition, and adequate and regular physical activity are factors that can directly improve immune fitness [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Therefore, in terms of pandemic preparedness, attaining a normal, healthy BMI should be viewed as one of several measures that could be adopted by individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Besides advanced pharmacological treatments, non-pharmacological interventions have gained attention to assist in combating primary and secondary events of COVID-19 ( 9 , 10 ). In this regard, dietary habits are critical due to their long-term physiological necessity ( 11 ).…”
Section: Introductionmentioning
confidence: 99%